INFORMATION SYSTEM HERBS INDONESIA BASED MOBILE APPLICATIONS - Nurbaiti Nurbaiti; Deltia Resty Fauziyah (STMIK Pringsewu Lampung, 2020)
Lack of information about herbal processing plants is a major problem in most Indonesian people. In addition to being one of the easy drugs to makeup at home, herbal plants Also include cheap and safe drugs because of the lack of side effects. Make it Easier for people to know the efficacy of herbal plants. The method used to design the system consists of Context diagrams and DFD level 0. For application design using appsgeyser. The results of testing this application can display the data on herbal plants and search for the data based on herbal names and Certain diseases.